The Influence of Fingerhold Technique and Positive Affirmation on Pain Reduction of Post Sectio Caesarea - Dewi, Adinda Putri Sari; Astuti, Dyah Puji; Kusumastuti, Kusumastuti; Wulandari, Rizki; Cahyandhika, Vega Dwi (Women, Midwives and Midwifery, 2025)
Background:Sectio caesarea (SC)  is a surgery that aims to give birth to a child through an incision in the abdominal wall and uterus. During sectio casa delivery, the mother will not feel pain, but pain will arise several hours after the procedure is completed. The pain felt by post SC mothers is a sharp pain, which spreads throughout the surgical treatment area. Objective: This study aims to analyze the Reduction in Pain Scale with the Fingerhold Technique and Positive Affirmation in Post SC Mothers at PKU Muhammadiyah Hospital, Gombong. Method: This quantitative study used a quasi-experimental design with a one group pre-test and post-test design. Sampling for this study used a purposive sampling technique. The sample of this study was 80 people who had met the inclusion and exclusion criteria. The instruments used were a questionnaire for the SOP for providing Fingerhold technique interventions, SOP for positive affirmations and a pain scale assessment sheet using the Numeric Rating Scale (NRS). Data analysis used univariate analysis, bivariate analysis was used to test the hypothesis with the Wilcoxon Test. Results: The results of the study showed a decrease in pain after being given the Fingerhold technique intervention and positive affirmations, as many as 14 respondents experienced changes in pain and 65 respondents experienced no changes in pain. Conclusion: The difference in pain before and after the intervention of fingerhold technique and positive affirmation, obtained significant results, meaning that there was a change in pain for the better in post-CS mothers, so it is worth considering as a policy by the hospital as one way to reduce pain in post-cesarean section.